The Case of a Rudderfish Highlights the Role of Natural History Museums as Sentinels of Bio-invasions - Brutto, Sabrina Lo (Zootaxa, 2017)
In September 2013 fishermen captured a rudderfish—Kyphosus vaigiensis—off Favignana Island, one of the islands of the Egadi Islands Marine Protected Area (MPA) in western Sicily (Mannino et al., 2015). This species is rarely sampled in the Mediterranean Sea.